Risk factors for wasting among hospitalised children in Nepal - Inoue, A; Dhoubhadel, BG; Shrestha, D; Raya, GB; Hayashi, Y; Shrestha, S; Edwards, T; Parry, CM; Ariyoshi, K; Cox, SE (BioMed Central, 2022)
Background: Malnutrition has various adverse effects in children. This study aimed to determine risk factors for malnutrition among hospitalised children, changes in nutritional status at admission and discharge and effects of use of systematic anthropometric measurement in identification of malnutrition.